A Novel Multimodal Therapy for Anaplastic Thyroid Carcinoma: 125I Seed Implantation Plus Apatinib After Surgery - Niu, Yiqi; Ding, Zheng; Deng, Xianzhao; Guo, Bomin; Kang, Jie; Wu, Bo; Fan, Youben (Frontiers in Endocrinology, 2020)
Abstract Anaplastic thyroid cancer is known to be the most lethal malignancy among endocrine tumors for its extremely limited survival after diagnosis. As a result of the poor survival prognosis, multimodal therapy is currently under investigation to address this global concern. In this reported case, the 125I seed implantation and vascular endothelial growth factor receptor-2 (VEGFR-2) inhibitor apatinib were co-applied to treat a 49-year-old woman with anaplastic thyroid cancer. After the patient began apatinib administration and underwent 125I seed implantation twice, the tumor size shrank successfully. After a follow-up of 13 months since the initial diagnosis of anaplastic thyroid cancer, the patient survived with stable disease pathology. In conclusion, this study supports 125I seed implantation and apatinib as effective therapeutic alternatives for inoperable anaplastic thyroid cancer patients.